Cystine import and oxidative catabolism fuel vascular growth and repair via nutrient-responsive histone acetylation - Drekolia, Maria-Kyriaki; Mettner, Janina; Wang, Daiyu; Delgado Lagos, Fredy Andrés; Koch, Christian; Hecker, Dennis; Eresch, Jeanette; Mao, Yifang; Bähr, Marion; Weichenhan, Dieter; Cordero, Julio; Wittig, Janina; et al. (Cell metabolism, 2026)
Endothelial metabolism underpins tissue regeneration, health, and longevity. We uncover a nuclear oxidative catabolic pathway linking cystine to gene regulation. Cells preparing to proliferate upregulate the SLC7A11 transporter to import cystine, which is oxidatively catabolized by cystathionine-γ-lyase (CSE) in the nucleus. This generates acetyl units via pyruvate dehydrogenase, driving site-specific histone H3 acetylation and chromatin remodeling that sustain endothelial transcription and proliferation. Combined loss of SLC7A11 and CSE abolishes cystine oxidative and reductive metabolism and causes embryonic lethality, whereas single deletions reveal distinct effects. SLC7A11 deficiency triggers compensatory cysteine de novo biosynthesis, partially maintaining angiogenesis, while CSE deletion disrupts nuclear cystine oxidative catabolism, transcription, and vessel formation. Therapeutically, cystine supplementation promotes vascular repair in retinopathy of prematurity, myocardial infarction, and injury in aging. These findings establish the role of cystine nuclear oxidative catabolism as a fundamental metabolic axis coupling nutrient utilization to gene regulation, with implications for vascular regeneration.
Online verfügbar: 31. Oktober 2025, Artikelversion: 6. Januar 2026
Gesehen am 26.02.2026